Karakteristik Dan Uji Fitokimia 5 (Lima) Jenis Tumbuhan Buah Eksotik dari Kabupaten Barito Utara Kalimantan Tengah - Milad Madiyawati; Penyang Penyang; Fouad Fauzi; Antonius Triyadi (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2017)
This study was conducted to identify the characteristics of fruit plants (generally, the environment/habitat and plant morphology fruit) and to determine the content of active compounds (secondary metabolites) plant worth exotic fruit contained in North Barito. This study used survey methods and data analysis was done descriptively qualitative and quantitative in tabular form and image. The results of the study characteristics and phytochemical test five (5) pieces of exotic plant species in North Barito regency from habitat plant fruit trees and lianas, with the composition of single and compound leaves, plant height of 10-15 meters, a lowland forest habitat. Keledang (Artocarpus lanceifolius Roxb) and Dangu (Leukconitis corpidae) which has a white sap. The test results showed the phytochemical content of secondary metabolites consisting of tannin (polyphenols), alkaloids, saponins, flavonoids, steroids and terpenoid scattered on the rind, pulp, and seeds.